The relevance of amenities and agglomeration for Dutch housing prices - Harry Garretsen; Gerard Marlet (Center for Economic Studies and ifo Institute (CESifo), 2011)
Dutch cities which combine a favourable location in terms of distance to work with a variety of urban amenities appear to be the most attractive locations for people to live. Relatively safe cities, offering a variety of history and culture events, as well as good restaurants have significantly higher housing prices. In addition, successful cities are places where people can optimize their job prospects, not necessarily only as a result of jobs in these cities, but also because of access to jobs in other Dutch cities.
Keywords: R11; 330; urban amenities; population growth; housing prices